The Evaluation of Career Centre Management at Health Colleges: A CIPP Model Approach - Putu Gede Subhaktiyasa; I Gede Ratnaya; Muhamad Nazim; Bayangkari Bayangkari; Made Ani Suprapta (Jurnal Basicedu, 2022)
The career center is one solution in responding to the high unemployment rate with higher education which is possible due to a mismatch between educational competence and the needs of employment, or an imbalance between demand and supply. The purpose of this study was to determine the success and effectiveness of the implementation of the career center program at one of the universities in the health sector in Denpasar City. This study is an evaluation study using the CIPP model which was analyzed qualitatively. The results show that in the context aspect it is necessary to set clear vision, mission, and goals. The input aspect shows that there is no curriculum as a guide and the implementation of several programs has not been optimally assessed from the process aspect. Meanwhile, the product aspect shows good acceptance of graduates in the world of work. It is hoped that the career center program can be improved by implementing strategic management and providing entrepreneurship education.